Nanoparticle-mediated down-regulation of TWIST increases radiosensitivity of nasopharyngeal carcinoma cells via ERK pathway - Zhuo, Xianlu (Am J Cancer Res, 2015)
Evidence suggests that over-expression of TWIST, an epithelial-mesenchymal transition inducer, might have a correlation with cancer progression and chemoresistance. However, its roles in radioresistance of cancer have rarely been reported. High TWIST expression was detected in nasopharyngeal carcinoma (NPC) and associated with poor prognosis. Thus, in the present study, we aimed to determine whether knockdown of TWIST can increase radiosensitivity of NPC cells. Chitosan-encapsulated TWIST-siRNA nanoparticles were constructed and used to silence TWIST expression in CNE2 cells. The cell viability and apoptosis as well as possible MAPKs pathways were assessed after irradiation treatment. The results showed that the nanoparticles successfully suppressed TWIST expression in CNE2 cells, and TWIST depletion significantly sensitized CNE2 cells to irradiation by inducing activation of ERK pathway but not JNK or p-38 pathways. The data suggested that TWIST depletion might be a promising approach sensitizing NPC cells to irradiation. Further investigations are needed to confirm the results.